A nationwide population‐based longitudinal study mapping psychiatric disorders during lifetime in siblings to patients with bipolar disorder. (20th December 2020) - Vedel Kessing, Lars; Ziersen, Simon Christoffer; Andersen, Per Kragh; Vinberg, Maj
Abstract: Objective: The aim was to map rates and cumulative incidences of psychiatric disorders during lifetime for siblings to patients with a diagnosis of bipolar disorder compared with the general population. Methods: Danish nationwide population‐based longitudinal register linkage study including 13, 923 unaffected siblings to 19, 955 patients with bipolar disorder and 278, 460 unaffected control individuals from the general population matched according to year of birth and sex. Follow‐up covered 22 years from 1995 to 2017. Results: Rates of 'any psychiatric disorder' among siblings compared with control individuals were constantly around twofold increased throughout lifespan whereas there was a bimodal age distribution of hazard ratios of bipolar disorder, unipolar disorder and use of alcohol or psychoactive drugs with the highest hazard ratios up to age 20 and above 60 years of age. Cumulative incidences from age 15 years of any psychiatric disorder were 44.2% at age 80 years for siblings versus 27.6% for control individuals and the corresponding numbers for bipolar disorder was 8.7% for siblings compared with 1.6% for control individuals. Conclusion: Strategies to prevent onset of psychiatric illness in individuals with a first‐generation family history of bipolar disorder should not be limited to adolescence and early adulthood but should be lifetime, likely with differentiated age‐specific strategies.